Analisis Multiplier Effect dan Dampak Ekonomi Objek Wisata Pantai Base-G terhadap Perekonomian Lokal di Jayapura - Marisa Christin Simbiak (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Base-G Beach is a tourist attraction located in North Jayapura District, Jayapura City, managed by the local community who hold customary land rights. This study aims to assess the economic impact of Base-G Beach using the multiplier effect analysis and to evaluate service quality based on the perceptions of visitors, business actors, and workers using a Likert scale. The assessment of six service aspects revealed that most were rated as very good, except for the availability of toilets and electricity, which still require attention. Regarding the economic impact, the Keynesian Income Multiplier calculation yielded a value of 0.27, indicating that the economic impact of this tourist attraction is still suboptimal. This value is below 1, meaning the tourism sector at Base-G Beach has not yet had a significant influence on the local economy. However, the Income Multiplier Ratios for Type I and Type II were 1.09 and 1.11, respectively, indicating a positive economic connection (≥1) between the tourism sector and the local economy. This suggests that there is potential for greater economic impact if the tourism sector is further developed. Nevertheless, the low Keynesian multiplier value indicates the need to strengthen the link between the tourism sector and the local economy. Therefore, it is recommended that the development of Base-G Beach tourism focus on improving infrastructure, particularly the provision of essential facilities such as toilets and electricity. Additionally, efforts should be made to expand the local economic network directly connected to the tourism sector. Improving service quality and developing infrastructure will help increase the economic impact of the tourist attraction, open new business opportunities, and provide greater benefits to the welfare of the surrounding community of Base-G Beach.